DNA and RNA : Understanding Genetics - Matthews, Samantha (United States : Larsen and Keller Education, 2022)
Genetics is the study of genes, heredity and genetic variation in living organisms. RNA and DNA are nucleic acids and form two of the four major macromolecules essential for all known life forms. DNA carries genetic information that is important for the functioning, development, reproduction and growth of organisms. It is formed by two chains that are coiled around each other forming a double helix whereas RNA is a single stranded molecule. RNA plays an important role in coding, decoding, regulation and expression of genes. It is used to convey genetic information and transmit cellular signals. It carries information from the DNA to ribosome where protein is synthesized in the cell. This book is compiled in such a manner, that it will provide an in-depth knowledge about the theory and practice of this discipline. It also elucidates the concepts and innovative models around prospective developments with respect to the field of genetics. Coherent flow of topics, student-friendly language and extensive use of examples make this book an invaluable source of knowledge.
Includes index.
Includes bibliographical references.
Keywords: Medical jurisprudence; DNA; RNA; Molecular evolution; Biotechnology; Nucleic acids; Molecular biology; Human genetics